THE LEARNING TRAJECTORY OF NUMBER PATTERN LEARNING USING BARATHAYUDHA WAR STORIES AND UNO STACKO - Risdiyanti, Irma; Prahmana, Rully Charitas Indra (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
In recent years, several researchers have tried to use stories and games as a starting point for learning mathematics. This is allegedly able to increase students' mathematical abilities and make learning mathematics more enjoyable. Therefore, this research is aimed to design a mathematics learning trajectory in pattern number using Barathayudha War Stories and Uno Stacko games as a starting point or context in the learning process with the Indonesian Realistic Mathematics Education (IRME) approach. The research method used is a design research that contains three stages, preliminary design, teaching experiment, and retrospective analysis. The result of this research is the learning trajectory design of number pattern learning using Barathayudha war stories and Uno Stacko. The design consists of four activities, which is a detective of Barathayudha war; rebuilt Abimayu fortress at the battlefield of Kurusetra; find the unique secret number code of Abimayu fortress; and built another fort using number pattern. The results showed Barathayudha war stories and Uno Stacko can stimulate students to understand their knowledge of pattern number concept which is the stages in the learning trajectory of student have an essential role in understanding the concept.